Notice of Cists recently discovered on the Sea-shore at Lundy in Fife (Proceedings of the Society of Antiquaries of Scotland, 1862)
This article discusses some of the stone cists that were uncovered by workmen in a quarry. It is noted that several other coffins have previously been found nearby. Although two of the cists were found at different depths, the author concludes that they were likely buried around the same time, possibly coinciding with a historical battle.